The Secret Society: o jogo social como contexto digital do ensino e da aprendizagem da língua inglesa - Oliveira, Jussara Candida Correia de (2018)
This dissertation is the resulted about the importance of a social game, The Secret Society, present in the digital social networking Facebook, and the teaching and learning process of the English Language by high school students of a public school located in the city of Santa Rita - PB. The research problem of this investigation is to analyze how a social game, present in the social networking Facebook, can be used to improve the development of the language skills necessary for teaching and learning the English language. Researchers of this field of study have developed a wide-ranging researches with authors who work in this line of investigation: Moita (2006), Gee (2009), Lévy (1995), Prensky (2001), Santaella (2013), Wenger and Briggs (2004), Alves (2008), Fava (2014), Mattar (2010), Paiva (2012) and Santos (2012). The research is qualitative, exploratory descriptive and is based on a case study based on the studies of Bogdan and Biklen (1994) and Gil (2002). The results show that the skills of the digital game, present in the social networking Facebook, contribute to the development of vocabulary and grammar skills within the contents for the series studied, promote ubiquitous learning, actions and principles of Communities of Practice inserted in the context of teaching and learning English. With this purpose, we offer to the mediator teachers of our society the technology, Screencast, with a tutorial to produce lessons using the digital social game, The Secret Society, which also presents adaptations of other games and different contexts for the optimization of teaching and learning.